Better perioperative outcomes in thoracoscopic-esophagectomy with two-lung ventilation in semi-prone position - Cai, Lei; Li, Yan; Sun, Li; Yang, Xue-Wen; Wang, Wen-Bin; Feng, Fan; Xu, Guang-Hui; Guo, Man; Lian, Xiao; Zhang, Hong-Wei (Journal of Thoracic Disease; Vol 9, No 1 (January 24, 2017): Journal of Thoracic Disease, 2017)
Background: One-lung ventilation (OLV) anesthesia intubation route is often used in patients undergoing thoracoscopic-esophagectomy in semi-prone position. Recently, the two-lung ventilation (TLV) approach becomes popular. However, limited studies have compared the two ventilation approaches in parallel. Here, we report a single-center, retrospective study of comparing TLV and OLV approach in patients undergoing thoracoscopic-esophagectomy in semi-prone position. Methods: From January 2013 to November 2014, 147 patients were enrolled into the current study and were given thoracoscopic-esophagectomy in semi-prone position either by OLV or TLV. Intraoperative respiratory functional data and perioperative surgical parameters of the two approaches were collected and analyzed. Results: Of the 147 patients, 64 patients received OLV and 83 patients received TLV, and all of them were successfully under gone thoracoscopic procedures without conversion to open thoracotomy. There was no incidence of major intraoperative complications or perioperative death. There were no statistically different in postoperative respiratory complications, either. However, TLV approach resulted in better intraoperative respiratory function (PaCO2, PaO2, SaO2), shorter preparation time for anesthesia induction, less blood loss, shorter thoracoscopic operating time and less postoperative hospital stay (P0.05). Conclusion: This study demonstrated that TLV intubation approach is superior to OLV approach during the thoracoscopic-esophagectomy in semi-prone position. According to this, TLV approach is a technically feasible, convenient and safe anesthesia induction approach for esophageal cancer surgery.